The appetizersand entrancesinthesectorof the restoration - del Toro Cabrera, Aureliano (Revista Universidad de Guayaquil, 2016)
The knowledge is associated with medical science which determine that exists a great dichotomy in appetizers and entrees. Usually these terminologies are used by professionals to identify the same thing, when actually two services or offers well demarcated from each other. According to criteria of medicine the gastric secretion (very important in digestion) which is produced in three phases named mental or cephalic, gastric and intestinal. The psychic or cephalic begins when the brain is activated through stimuli which produce the sense of small and sight, evoking a determined food and even drink some soft drinks and receive an order to operate the digestive system. In gastric phase the crucial thing is to eat small food portion which should facilitate secretion of gastric juices. Taking into consideration the physiological functioning of the body, everything what is ingested firstly should guarantees the possibility to create a brain stimuli, appetizers, and afterwards prepares a stomach to carry out with an efficient digestion with the arrival of bolus (entrees). Consecrating the products which are included in the restaurant’s menu respond on various factors which should not be a barrier and rigid, cause this study proposes reflections and we should be aware the time of confection.
Keywords: appetizers; entrees; gastric secretion; cephalic phase; gastric phase